(untitled) (CAHIERS MAGELLANES-NS, 2024)
This research paper deals with the refugee influx from the East Pakistan to the different areas of western Assam during Bangladesh liberation movement. In case of Bangladeshi refugees, the Indian states responded with alacrity in order to come to terms with a grave crisis. During the Bangladesh liberation war with West Pakistan, an estimated ten million people of East Pakistan (present-day Bangladesh) crossed the international border, fled the country and took refuge in India particularly in the Indian states of West Bengal and Indian North East region, especially Tripura and Assam. The Government of Assam’s approach towards these refugees in terms of providing shelter and relief will be of prime emphasis in this research paper.